Зміна анатомічних показників листків Platanus orientalis L. під дією промислових емісій (техногенного навантаження) - Kapelyush, N.V.; Bessonova, V.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The parameters of anatomic structure of leaves of Platanus orientalis L. have grown in the conditions of aerogenic pollution of various quality and intensity were studied and compared. The authentic difference of values of dimensional parameters of anatomic structure of leaves were found in control and test plots. The increase of pollution causes the changes directed on strengthening xeromorphism.